2001
DOI: 10.1007/bf03186081
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on high temperature steam oxidation of zircaloy-4

Abstract: The pressure effects on the oxidation of Zircaloy-4 (Zry-4) cladding in high temperature steam have been analyzed. A double layer autoclave was made for the high pressure/high temperature oxidation tests. The experimental test temperature range was 700-900 o C, and pressures were 0.1-15 MPa. Steam partial pressure was found to be a more important factor than total pressure. Steam pressure enhances the oxidation rate of Zry-4 exponentially and depends on the temperature, the maximum being between 750-800 o C. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With the exception of a few specific conditions (post-breakaway oxidation at temperatures typically lower than 1050°C [4] [15][16] [20] [21], oxidation under high steam pressures [22] [23] or secondary hydriding due to steam starvation inside the cladding after ballooning and burst [24] [25]), as-received zirconium alloys do not absorb a significant amount of hydrogen when oxidized in steam at HT [26]. Hydrogen pickup during oxidation in steam at HT is not provided in most papers dealing with the oxidation of pre-oxidized zirconium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of a few specific conditions (post-breakaway oxidation at temperatures typically lower than 1050°C [4] [15][16] [20] [21], oxidation under high steam pressures [22] [23] or secondary hydriding due to steam starvation inside the cladding after ballooning and burst [24] [25]), as-received zirconium alloys do not absorb a significant amount of hydrogen when oxidized in steam at HT [26]. Hydrogen pickup during oxidation in steam at HT is not provided in most papers dealing with the oxidation of pre-oxidized zirconium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms causing the breakaway oxidation are still unclear. Several explanations have been suggested in the literature such as the destabilizing effect of the tetragonal-to-monoclinic phase transformation in the oxide layer [11,16,17]. A recent study using HT XRD analysis demonstrated that this phase transformation is not the main cause of the breakaway oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to [7,9], when an adequate supply of steam is provided, the steam and hydrogen partial pressures have no effect on the weight gain. Moreover, when studying the oxidation of Zircaloy-4 samples in steam/argon mixtures with total pressures of 7.5 and 10 MPa, it was found that the oxidation rate is sensitive to the steam partial pressure and not to the total gas pressure [16,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, today the mechanisms at the root of this behavior are still unclear. One of the main possible explanations proposed in the literature is the tetragonal-to-monoclinic phase transition of zirconia [8,[13][14][15][16]. Other explanations found in the literature are the stress relaxation in the oxide when it reaches a critical thickness [13,17] and the evolution of the oxide morphology during oxidation leading to the formation of a short circuit of oxygen via micro-pores [18,19].…”
Section: Introductionmentioning
confidence: 99%